Credit For Export Bow Penetration: Catalyzing A Breakthrough In The International Trade Sector - Charles, Gerald Ezra; Rangen Jaya, Magnus Hosea (Journal of Sustainable Economics, 2023)
International trade, especially through exports, can certainly be an alternative to overcome the various uncertainties that arise due to the Covid-19 pandemic. Unfortunately, in boosting Indonesia's export performance, Indonesia is still faced with the main problem, the narrowness of the export destination market is also a problem that makes Indonesia very dependent on the economic conditions of the main trading partner countries. Credit for Export Penetration is mainly a loan provided to finance export activities to non-traditional markets. Credit for Export Penetration also utilizes collaboration across stakeholders including the Ministry of Trade, Ministry of Industry, trade attache, and ITPC.